Peroneal nerve injuries during anterior ankle arthroscopy - Jorge Pablo Batista; Guillermo Martin Arrondo; Germán Matías-Joannas; Lucía Verónica Cangiano; Rafael Baraousse; Leandro Casola; Miki Dalmau-Pastor (Journal of the Foot & Ankle, 2022)
Objective: Ankle arthroscopic surgery is considered a safe procedure with minimal risk of peripheral nerve injury. The primary objective of this study was to determine the incidence of peripheral nerve injuries during anterior ankle arthroscopy. The secondary objective was to evaluate the most frequent types and the clinical relevance of deep peroneal nerve injuries. Methods: Patients who underwent anterior ankle arthroscopy at our institution from 2000 to 2020 were retrospectively analyzed. Those present neurological symptoms after surgery were evaluated with clinical examination and ankle ultrasonography looking for nerve injuries. Results: Three hundred and thirty-four patients were included in the present study. There were 26 iatrogenic neurological complications (7.78%). The superficial peroneal nerve was injured in 16 cases (4.79%) and the deep peroneal nerve, in 10 cases (2.99%). Among the injuries of the deep peroneal nerve, 1.5% of cases had nerve entrapment in postoperative tissue adhesions, 0.9% presented neuromas, and 0.6% had axonotmesis. Complications were classified using the Modified Clavien-Dindo-Sink Complication Classification System: 2.1% of complications were grade I, while 0.9% were grade II. Conclusion: Nerve injury is the most common complication related to anterior ankle arthroscopy. The deep peroneal nerve is rarely damaged during this procedure. We found that most deep peroneal nerve injuries are not clinically relevant and do not have a big impact on patient evolution during the postoperative period. Level of Evidence II; Retrospective Study; Prognostic Studies.